Injuries in Thai Boxing - Elżbieta Sieńko-Awierianów; Łukasz Orłowski; Monika Chudecka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
As with many other combat sports, Thai boxing requires high levels of exertion which may result in various injuries. Their types and extent determine the nature of help required during rehabilitation. The aim of the study was to assess the risk of injury and indicate factors causing injury in Thai boxing. To this end, we conducted asurvey among the members of the Nauk Muay Association of Physical Culture in Szczecin. Our respondents reported inappropriate technique as the most common cause of injuries. The second leading cause of injuries was an excessively ambitious approach in training. Injuries – most frequently bruises in lower extremities – were most often sustained during sparring. The incidence of injury was statistically significantly related to male gender and sporting experience; men were also most likely to sustain bruises from all types of trauma.